Pengaruh Media Pembelajaran Interaktif Terhadap Literasi Membaca Pada Pembelajaran Bahasa Indonesia Kelas III di SDN 03 Mamben Lauk - Hafizin, Muhammad; Hasanah, Niswatul; Agustina, Sri (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
The education in Indonesia is currently experiencing enormous This research aims to describe the effect of interactive learning media on reading literacy in Indonesian language learning carried out at SDN 03 Mamben Lauk for class III students in the even semester of the 2023/2024 academic year with a population of 39 students. Sampling was carried out using random sampling technique. This research is a Quasi Experimental Design research with a Nonequivalent Control Group Design experimental research design. Research data on interactive learning media and reading literacy were collected through pre-test and post-test. The data obtained was then analyzed using the SPSS application. The results of this research are that the reading literacy ability of class III students at SDN 03 Mamben Lauk for the 2023/2024 academic year is in the medium category. Based on hypothesis calculations using SPSS, at a significance level of 5%, t = 0.046 and a significance level of 5%. Therefore, t count (0.046) < t table (0.05:14) is 1.761, then Ha is accepted. This shows that the variable interactive learning media on reading literacy in Indonesian language learning has an influence, so that Ha is accepted and Ho is rejected, which means there is a significant positive influence between interactive learning media on reading literacy in class III Indonesian language learning at SDN 03 Mamben Lauk.